RISK-BASED LIFE CYCLE COST ANALYSIS FOR STRATEGIC MAINTENANCE DECISION-MAKING IN DEEPWATER GAS OPERATIONS - Febri Rio Cahyono; Pri Hermawan (RADJA PUBLIKA, 2026)
This paper examines why the maintenance cost per barrel at a deepwater gas field operating under a cost-recovery production-sharing contract rose 161% in a single year, climbing from USD 0.41/BOE in the prior year to USD 1.07/BOE, even though plant availability stayed above 97%. A risk-based life-cycle cost (LCC) framework is applied to four maintenance strategy alternatives over an eight-year residual contract horizon (2025 to 2032) using primary operational records for 2021 to 2024, supplemented by sensitivity analysis and the Analytic Hierarchy Process (AHP). The deterministic Net Present Cost (NPC) ranking favors contract restructuring as the least-cost option (A2, USD 72.37M, 10% real discount rate). The multi-criteria evaluation, which integrates risk-cost exposure under the safety, efficiency, flexibility, and cost criteria (weights 0.557, 0.286, 0.100, 0.056, CR 0.003), supports condition-based monitoring investment as the recommended strategy (A3, NPC USD 74.51M, AHP composite 0.438). An expected-value analysis estimates that a CBM-enabled 30% reduction in unplanned-event frequency avoids approximately USD 5.9M of production-loss exposure against a USD 2.14M premium over the cheapest alternative, a ratio of roughly 2.8 times. The recommended strategy targets a return to USD 0.85 to 0.90/BOE within the 2026 to 2028 planning horizon. The findings show that under cost-recovery fiscal structures, the cost-cheapest option is not the value-best option once risk-cost exposure is properly weighted.